Relationship between Clinicopathological Characteristics and Survival Rate in Patients Colorectal Cancer - FR. Aditya Pradatasari; Pratika Yuhyi Hernanda; Maria Widijanti Sugeng; Inawati Inawati (Journal La Medihealtico, 2026)
The survival rate in colorectal cancer patients is influenced by factors that contribute to the individual diagnosed with colorectal cancer, including clinicopathological characteristics such as cancer location, histopathology, degree of differentiation, and cancer metastasis. This study aims to analyze the relationship between clinicopathological characteristics of colorectal cancer and the survival rate of colorectal cancer patients at RT Notopuro Sidoarjo Regional Hospital. Research methods used use observational analytic with design Cross-sectional. The results of this study showed that 53.8% of male colorectal cancer patients were aged >60 years, the most common location was in the colon (61.5%) with a good grade type, and no metastases in other organs (65.4%). From the results of the Kaplan Meier curve, it can be seen that there is a tendency that cancer locations in the colon, which are well differentiated, and which do not experience metastasis have a longer survival rate compared to cancer locations outside the colon, which are moderately-poorly differentiated, and which experience metastasis, although the results of the statistical analysis show an insignificant relationship (p-value>0.05).